HOMOLOGY MODELING AND IN SILICO DOCKING ANALYSIS OF HUMAN MITOCHONDRIAL THYMIDINE KINASE 2 USING GRID-BASED LIGAND DOCKING WITH ENERGETICS - Mahendran, Radha; Jeyabasker, Suganya; Manoharan, Sharanya; Krishnan, Anbarasu; Francis, Astral (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective:Mitochondrial disorders linked to Thymidine Kinase 2 (TK2) deficiency is associated to long term treatment with antiviral nucleoside analogues such as AZT (AZidoThymidine). The accumulation of AZT-TP (AZidoThymidine-TriPhosphate) is suggested to affect DNA polymerase, resulting in mtDNA (mitochondrial DNA) depletion. Thus a potent and selective inhibitor for TK2 is essential to be predicted. Methods: The human mitochondrial TK2was modeled usingModeller and the structure was evaluated using Ramachandran plot. The ligand molecule of both the derivatives of deoxythymidine and thioureawere optimized usingChemsketch and were further docked using GLIDE SchrÃ¶dinger package 2009. Results: The docking results of both Deoxythymidine and Thiourea derivatives against the target TK2 were analyzed to find the ligands with good dock score and Glide energy. The ligands were selected and induced fit docking of both the derivatives were carried out and the interactions were observed usingPyMol. Conclusion: The present study indicates that deoxythymidine derivatives interact significantly and hence serve as selective inhibitors against Human Mitochondrial TK2. Â 